Defense Mechanisms of Locke Lamora Character in Scott Lynch’s The Lies Of Locke Lamora - SIjabat, Yusuf Febby; Heriyati, Nungki (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
The research aims to explore into defense mechanism used by Locke Lamora, the protagonist of Scott Lynch’s The Lies of Locke Lamora, using a psychoanalytic approach. The research, which is based on Anna Freud’s defense mechanism theory, try to understand how Locke’s psychological defense contributes to his complex identity. The qualitative method of close reading is used on chosen dialogues and narrative section, with a focus on recurring patterns of humor, rationalization, sublimation, denial, projection, and reaction formation. The findings show that Locke has developed defenses as adaptive mechanism that protect him against feelings of guilt, loss, and dread hence his strength, resilience and vulnerability. His tendency to rationalize crimes and injustice, covering up pain with humor, and transform impulse into something artistic demonstrates the ego’s constant effort to maintain order in corrupt place. The research contributes to literary psychology by demonstrating how defense mechanisms function not just as psychological strategies but also as narrative devices, maintaining Locke’s moral ambiguity which defines his character. Keywords: Psychoanalysis, Moral Code, Characters, Defense Mechanism